2011
DOI: 10.1108/13552541111156450
|View full text |Cite
|
Sign up to set email alerts
|

The investigation of the influence of laser re‐melting on density, surface quality and microstructure of selective laser melting parts

Abstract: Purpose -Selective laser melting (SLM) is a powder metallurgical (PM) additive manufacturing process whereby a three-dimensional part is built in a layer-wise manner. During the process, a high intensity laser beam selectively scans a powder bed according to the computer-aided design data of the part to be produced and the powder metal particles are completely molten. The process is capable of producing near full density (,98-99 per cent relative density) and functional metallic parts with a high geometrical f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
115
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 316 publications
(139 citation statements)
references
References 22 publications
(21 reference statements)
6
115
0
Order By: Relevance
“…Laser re-melting (outer contour and inner contour parameters) were used in this study so that sample shell strength could be improved, better surface quality achieved, while at the same time retaining a high internal porosity. This result agrees with the findings of other studies, in which laser re-melting can improve the density and enhance the surface roughness of printed parts [35,40,41]. From these findings, the high porosity parts, which were generally printed using an energy density less than 2.00 J/mm 2 , might not print well if their shells were too weak.…”
Section: Discussionsupporting
confidence: 82%
“…Laser re-melting (outer contour and inner contour parameters) were used in this study so that sample shell strength could be improved, better surface quality achieved, while at the same time retaining a high internal porosity. This result agrees with the findings of other studies, in which laser re-melting can improve the density and enhance the surface roughness of printed parts [35,40,41]. From these findings, the high porosity parts, which were generally printed using an energy density less than 2.00 J/mm 2 , might not print well if their shells were too weak.…”
Section: Discussionsupporting
confidence: 82%
“…3). This similar geometry was used in previous works [16,19], because it allows the surface roughness for each inclination angle to be easily measured. Figure 4 illustrates the characteristic surface morphologies of SLM processed titanium alloy representative parts observed at a relatively low magnification produced under the first set of parameters given in Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…Also, the roughness of top surface differs strongly from the roughness of side surfaces [15,17,18]. To overcome this problem, a variety of surface modification techniques are available in the market including mechanical processes, chemical processes, and thermal processes [1,16,19,20]. In this study, experimentally selected SLM process conditions and orientation of models made by Ti-6Al-4V alloy to ensure a minimum average and total roughness values.…”
Section: Surface Quality Research For Selective Laser Melting Of Ti-6mentioning
confidence: 99%
See 1 more Smart Citation
“…Dividing a part into shell and core sections with an overlap between them may not only reduce the edge heights, but also address the contour scanning issue. Moreover, Yasa et al (2011) also found that laser re-melting is a promising method to increase the density to almost 100% and to enhance the surface quality of SLM parts.…”
Section: Scanning Strategymentioning
confidence: 96%